2020
DOI: 10.2147/cia.s253262
|View full text |Cite
|
Sign up to set email alerts
|

<p>Is Handgrip Strength a Useful Measure to Evaluate Lower Limb Strength and Functional Performance in Older Women?</p>

Abstract: This study aimed to determine the association of handgrip strength with isometric and isokinetic strength (hip, knee and ankle extensor/flexor muscles), and functional capacity in older women. Methods: The handgrip strength and lower limb strength of 199 older women (60-86 years) were measured using JAMAR and BIODEX dynamometers, respectively. Time Up and Go, Five-times-sit-to-stand and 6m-walk functional tests were evaluated. Pearson correlations were used to determine the relationship between variables. Regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…To date, the handgrip evaluation represents the most common test used to measure this physical capacity [63] due to its high affordability, portability, simplicity, and test-retest repeatability [64]. Nevertheless, to obtain an overall indicator of strength, some investigations have suggested the need to complement this test with specific evaluations of the lower-limb muscles (e.g., isometric knee extension) [65][66][67]. The present study found that individuals suffering from (pre-) sarcopenia or (pre-) frailty significantly improved both handgrip (ES = 0.51, p = 0.001) and lower-limb (ES = 0.93, p < 0.001) strength after a training intervention based on resistance exercises.…”
Section: Muscular Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the handgrip evaluation represents the most common test used to measure this physical capacity [63] due to its high affordability, portability, simplicity, and test-retest repeatability [64]. Nevertheless, to obtain an overall indicator of strength, some investigations have suggested the need to complement this test with specific evaluations of the lower-limb muscles (e.g., isometric knee extension) [65][66][67]. The present study found that individuals suffering from (pre-) sarcopenia or (pre-) frailty significantly improved both handgrip (ES = 0.51, p = 0.001) and lower-limb (ES = 0.93, p < 0.001) strength after a training intervention based on resistance exercises.…”
Section: Muscular Strengthmentioning
confidence: 99%
“…These findings could be strongly related to the significant lower-limb strength gains (Figure 3). Since the lower-limb muscles (e.g., knee extensors) are mainly responsible for actions such as chair rising or walking [68][69][70], the increment of strength in these structures could have been positively transferred into the physical function. In turn, these improvements in physical function can potentially reduce the dependency situation of older adults, thus increasing their quality of life [71] and decreasing the public health costs [72,73].…”
Section: Physical Functionmentioning
confidence: 99%
“…Although the handgrip strength served as an independent predictor to assess ADL performance, it is not a useful measurement to evaluate lower-extremity strength [34]. Our results further validate that the handgrip strength test is not suitable to detect early LS (stage ).…”
Section: Discussionmentioning
confidence: 64%
“…The average value was calculated after the second measurement. Handgrip strength of the dominant hand was measured by handgrip dynamometer (JAMAR@Plus) for 3 times, and the maximum handgrip strength was taken for analysis [ 11 , 12 ]. Participants stood with their feet shoulder width apart and the calf circumference around the most prominent part of the gastrocnemius muscle was measured (accurate to 0.1 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Handgrip strength of the dominant hand was measured by handgrip dynamometer (JAMAR@Plus) for 3 times, and the maximum handgrip strength was taken for analysis [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%